2019
DOI: 10.1508/cytologia.84.47
|View full text |Cite
|
Sign up to set email alerts
|

Cytological and Hybridization Studies in Three Cultivars of Tuberose (<i>Polianthes tuberosa</i> L.)

Abstract: Three cultivars of tuberose (Polianthes tuberosa L.), one having spikes with single type of flowers (Single), another with double type of flowers (Double) and the third with single flowers and variegated leaves (Variegated) had somatic chromosome number of 2n=60 and karyotypes comprising 10 long and 50 short chromosomes. The three cultivars, and hybrids of Single Double' and Variegated Single showed regular meiosis with the chromosomes paired into 30 bivalents at metaphase I (M I). These observations suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
3
2
0
Order By: Relevance
“…Pod set observed from the cultivars upon sel ng indicates their compatibility. The results derived supports the ndings of Karihaloo (2019) and Uma and Gowda (2000) that the tuberose variety Variegated is self-compatible. Apart from that, the other single-type tuberose lines like IIHR-6, Arka Nirantara, Arka Shringar were also found to be self-compatible with the highest seed set percentage upon self-pollination.…”
Section: Self-pollination Incompatibility and Pollen-pistil Interactionsupporting
confidence: 88%
See 3 more Smart Citations
“…Pod set observed from the cultivars upon sel ng indicates their compatibility. The results derived supports the ndings of Karihaloo (2019) and Uma and Gowda (2000) that the tuberose variety Variegated is self-compatible. Apart from that, the other single-type tuberose lines like IIHR-6, Arka Nirantara, Arka Shringar were also found to be self-compatible with the highest seed set percentage upon self-pollination.…”
Section: Self-pollination Incompatibility and Pollen-pistil Interactionsupporting
confidence: 88%
“…Florescence microscopic study on the pollen-pistil interaction indicated the presence of 'gametophytic self-incompatibility' in operation as reported by Karihaloo (2019); Ranchana and Kannan (2016) in tuberose. Stylar inhibitions were also reported by Ghosh and Shivanna (1980) in Linum grandi orum, Karihaloo (2019) in tuberose and Shimizu and Okada (2000) in Arabidopsis.…”
Section: Self-pollination Incompatibility and Pollen-pistil Interactionsupporting
confidence: 57%
See 2 more Smart Citations
“…It is one of the most popular and fragrant cut flowers grown in India as well as worldwide [3]. For single-stemmed tuberose, the basic chromosome number is 2n=60, whereas the chromosome number of double-flowered species have ranged from 2n=50 to 2n=54, 60 and 120 [4,5].…”
Section: Introductionmentioning
confidence: 99%